Early oncology clinical trial design in the era of molecular-targeted agents. (August 2010) - Brunetto, Andre T; Kristeleit, Rebecca S; de Bono, Johann S
The introduction of molecularly targeted agents has changed the concept of drug development. The field has evolved over the last decade and therapeutic drugs are now being rationally designed to affect specific intracellular or extracellular pathways that are thought to be important for cancer progression. Traditionally, toxicity has been the primary end point for dose definition and escalation; however, novel targeted compounds are characterized by the lack of significant clinical toxicity compared with conventional chemotherapy. Alternative trial designs and pharmacodynamic-driven biomarkers that assess drug-target effect and allow demonstration of proof-of-concept for intended target modulation and achievement of desired biological effects have emerged to guide dose selection. This must be facilitated by validated preclinical tumor models and biomarker assays that are critical to aid understanding of which agents are likely to be beneficial in different cancer subtype patients and which biomarkers should be implemented into early trial design.